2003
DOI: 10.1080/00365540310015872
|View full text |Cite
|
Sign up to set email alerts
|

How Safe is Safe? – A Case of Lactobacillus paracasei ssp. paracasei Endocarditis and Discussion of the Safety of Lactic Acid Bacteria

Abstract: We report a case of endocarditis due to Lactobacillus paracasei ssp. paracasei, which could be distinguished from Lactobacillus strains used for the fermentation of dairy products by randomly amplified polymorphic DNA-polymerase chain reaction. The safety of biotechnical lactic acid bacteria use is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…Furthermore, these bacteria are typically known to convey benefits to individuals and are widely consumed in yoghurts and as probiotics (Ouwehand et al, 2002). However, there is increasing evidence that particular lactic acid bacteria are of pathogenic relevance (Cannon et al, 2005) and are able to cause more severe diseases such as endocarditis (Soleman et al, 2003). In one of our own studies Lactobacillus iners was identified to contribute significantly to UTI (Domann et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these bacteria are typically known to convey benefits to individuals and are widely consumed in yoghurts and as probiotics (Ouwehand et al, 2002). However, there is increasing evidence that particular lactic acid bacteria are of pathogenic relevance (Cannon et al, 2005) and are able to cause more severe diseases such as endocarditis (Soleman et al, 2003). In one of our own studies Lactobacillus iners was identified to contribute significantly to UTI (Domann et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis has also been reported in adults, children, and infants who received probiotic supplements. 118,[124][125][126] Land et al 126 recently reported LGG probiotic sepsis occurring in immunocompromised infants and children. A medically fragile infant 6 weeks of age became septic with a strain of LGG that was being provided as a supplement.…”
Section: Safety Of Probiotics and Prebiotics In Infants And Childrenmentioning
confidence: 99%
“…Cases of serious infection have occurred and been reported in the literature. 10,[118][119][120][121][122][123][124][125] Patients at risk would be those who are immunocompromised, including ill preterm neonates, and/or children who have intravenous catheters or other indwelling medical devices. In most cases, the offending organism that caused the sepsis seems to have stemmed from bacteria from the individual's own endogenous flora.…”
Section: Safety Of Probiotics and Prebiotics In Infants And Childrenmentioning
confidence: 99%
“…Lactobacillus paracasei usually does not cause human disease [17] but is known to cause disease in animal models [18] and rarely among immunocompromised patients [19]. In this particular bacterium, few cases have been reported as the cause of human infections.…”
Section: Discussionmentioning
confidence: 99%